Black currant cultivars, developed at the Polli Horticultural Research Center (Estonia), in Northwest Russia - O. A. Tikhonova; V. S. Popov (Труды по прикладной ботанике, генетике и селекции)
Background. Introduction of new foreign cultivars makes it possible to expand the limits of the genetic potential of the VIR collection. A comprehensive study of such germplasm accessions is important for identifying sources of traits useful for breeding and the best cultivars for practical utilization. Materials and methods. Eight black currant cultivars released in Estonia were studied from 2015 through 2023 at Pushkin and Pavlovsk Laboratories of VIR. Conventional methods were used to test their adaptability and assess their main productivity indicators and berry quality. The resulting data were statistically processed in Microsoft Excel according to the guidelines by B. A. Dospekhov. Results and conclusion. The studied cultivars appeared well adapted to the environments of Northwest Russia. The heat supply in Leningrad Province is optimal for their cultivation. Good adaptability, synchronized fruit ripening, stable yields, and fine taste of berries were demonstrated by cvs. ‘Almo’ (k-44169), ‘Albos’ (k-44167), ‘Elo’ (k-44171), ‘Karri’ (k-44172), ‘Mulgi Must’ (k-38061), ‘Musti’ (k-44173), and ‘Varmas’ (k-44174). They are recommended for amateur gardens in Northwest Russia. Cv. ‘Karri’ (k-44172) is a promising source of such traits as good self-fertility, large fruit size, stable yield, well-balanced taste, high anthocyanin content in berries, and resistance to American powdery mildew and gall mite. Cv. ‘Varmas’ is a source of earliness, high self-fertility, and dessert taste of berries.